International refugee law and the protection of stateless persons - Foster, Michelle 1972-; Foster, Michelle, 1972- (Oxford University Press, 2019)
he book examines the extent to which the 1951 Convention relating to the Status of Refugees protects 'de jure' stateless persons. While de jure stateless persons are clearly protected by the 1954 Convention relating to the Status of Stateless Persons, this book seeks to explore the extent to which such persons are also entitled to refugee status. The questions addressed include the following: When is a person "without a nationality" for the purpose of the 1951 Refugee Convention? What constitutes one's country of former habitual residence as a proxy to one's country of nationality? When does being stateless give rise to a well-founded fear of persecution for reasons specified in the 1951 Refugee Convention and/or UNHCR mandate? What are the circumstances under which statelessness constitutes persecution or inhuman or degrading treatment? How are courts assessing individual risk or threat to stateless persons?